Student Interaction In Improving Speaking Ability At Nursing Study Program STIKES Ngudia Husada Madura - Dhaniel Prasetyo Irianto; Emi Nurniati (Departement of Mathematics Education, 2023)
This study aimed to determine the effect of student interaction on the improvement of English speaking skills. Interactions between students and other students as well as interactions between students and instructors will be analyzed. Interactions that occur both inside and outside of the classroom are crucial to both the learning process and the process of acquiring English. This study is qualitative and descriptive in nature. The learning process consists of a sequence of implementations by educators and students. In this case, there will be reciprocity between students and instructors in order to attain certain objectives. This relationship is known as interaction, and it can occur both inside and outside of the classroom. It is necessary for students to interact both inside and outside of the classroom to improve their English speaking abilities. The interaction includes question-and-answer exchanges, the exchange of ideas, and conversations. This includes interactions between students and instructors as well as interactions between students. This has been shown to enhance the English-speaking skills of STIKES Ngudia Hussada Madura students. Those who prefer to be passive make little to no progress in speaking English, in contrast to those who frequently engage in conversation.